Dermoscopic Features of a Black Hairy Tongue in 2 Japanese Patients - Ken Kobayashi; Yasuhiko Takei; Mizuki Sawada; Sumiko Ishizaki; Haruo Ito; Masaru Tanaka (Hindawi Limited, 2010)
Dermoscopic features of a black hairy tongue have never been reported. Dermoscopy might be useful in speculating pathologic features of oral lesions. The objective was to identify additional dermoscopic criteria. Two Japanese patients who were clinically given a diagnosis of "black hairy tongue" were evaluated for dermoscopic features. We have shown characteristic dermoscopic features of brownish hair-like elongation of filiform papillae with whitish lingual papillae. Dermoscopic examination seemed useful as an adjunct to the diagnosis of this benign disorder of the tongue, demonstrating exact changes in shape and color of filiform papillae. It might also be helpful in more objective observation of the therapeutic efficacy.